Using a blended learning approach to support women returning to STEM. (2nd January 2019) - Herman, Clem; Gracia, Rosaria; Macniven, Lesley; Clark, Bernie; Doyle, Geraldine
ABSTRACT: This paper examines a blended learning model designed to support women returning to STEM after a career break and its delivery in a unique partnership between an online distance education provider and a community-based equality organisation. Through this partnership additional activities such as networking events, returnships, career clinics and webinars were used in conjunction with a structured online Badged Open Course (BOC), which enabled a successful return to employment for many of the participants. This article outlines the results and implications of this integrated model and argues that blended learning approaches need to be flexible and adaptable to be able to incorporate the needs of learners at different life-course stages, taking into consideration gender and other diversity characteristics.